The Role of Using Betel Leaf in Pediatric Stoma Care in Bangladesh: A Prospective Study - Bipul Bhusan Das, Bipul Bhusan Das; Masud, Md. Sadruddin Al; Islam, Md. Tawhidul (The Insight, 2022)
Introduction: Construction of a stoma is a common procedure in pediatric surgical practice. For care of these stomas, commercially available devices such as ostomy bag, either disposable or of longer duration are usually used. These are expensive, particularly in countries like Bangladesh, and proper-sized ones are not always available. We have found an alternative for stoma care, betel leaf, which is suitable for Bangladeshis. Objective: The purpose of the study is to assess the role of using betel leaf inpediatric stoma care in Bangladesh. Method and materials: It is a prospective study conducted at the department of pediatric surgery, Dhaka Medical college and Hospital over a period of 24 months, January, 2014 to December, 2015, with a sample size of 60. Patients within 12 years having temporary loop colostomy or ileostomy in the pediatric surgery units of Dhaka Medical College & Hospital within the study period were considered as the study population.After construction of stoma, at first zinc oxide paste was applied on the Peristomal skin. A betel leaf with shiny, smooth surface outwards & rough surface inwards was put over the stoma with a hole made in the center according to the size of stoma. Another intact leaf covers the stomal opening. When bowel movement occurs, the overlying intact leaf was removed & the faecal matter was washed away from both. The leaves were reused after cleaning. Use of commercially available Ostomy bag (e.g., Convatec ostomy bag) with Adhesive paste (Stomahesive) will be applied on the Peristomal skin. Results: Of 60 pediatric patients, 20 had pelvic colostomy, 19 had transverse colostomy and 21 had ileostomy. Of 60 patients under stoma care Mild excoriation had seen 13.3% cases of betel leaf users. Out of 40% excoriation, 30% occurred in ileostomy (p value <0.0001, hence significant). Conclusion: No doubt, a commercial stoma appliance in the form of a well fitted stoma bag is need for proper care of a colostomy or ileostomy and the adjacent skin. But in underdeveloped country like Bangladesh, it is often beyond economic capability of parents to purchase stoma appliances regularly on a long-term basis. It is also not easily available in the small towns and rural areas of the country. In such a situation, the role of betel leaf are highly important and it can be used as a cheap, easily available, satisfaction on care givers to take care of stoma, nonirritant and effective alternative of appliances to care of a stoma and Peristomal skin in pediatric patients.